(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: The pattern of overexpression of p53 in RCC and their correlation with the histological types, Grading and pathological staging can guide the oncologist for selection of the patients. Objective: The aim of the study was to observe the pattern of overexpression of p53 in RCC and their correlation with the histological types, Grading and pathological staging. Methodology: This cross-sectional study was carried out in the Department of Pathology at Dhaka Medical College, Dhaka, Bangladesh from January 2018 to December 2019. Here 50 cases were selected as per inclusion and exclusion criteria. Histopathological investigations were done. Information were recorded in a prepared proforma. Results: Increased p53 expression was seen in 40.0% of the histologic sections. There is a significant association of p53 expression with some demographic variables (age and betel quid chewing), the tumor grading, pathological staging and tumor subtype (Papillary and clear cell type). It was also found that p53 expression was more prevalent in nonconventional (Papillary type). The p53 expression was observed in association with the presence of bad prognostic markers, like high tumor grading and staging. Conclusions: The expression of p53 is significantly associated with a number of bad prognostic factors in renal cell carcinoma. Journal of National Institute of Neurosciences Bangladesh, January 2022; 8(1):57-61